Rectal tuberculosis: A rare cause of recurrent rectal suppuration - Samarasekera, D. N.; Nanayakkara, P. R. (Wiley, 2008)
Tuberculosis affecting the rectum is a rare extrapulmonary form of the disease that needs recognition, because it requires specific treatment and avoids multiple, unwarranted surgical interventions. The following discussion is centred on a case of rectal tuberculosis, a disease that rarely affects the anorectal region. The condition was diagnosed on histology and was successfully treated medically with complete resolution